The effects of team identification on consumer purchase intention in sports influencer marketing: The mediation effect of ad content value moderated by sports influencer credibility - Jin Kyun Lee (Cogent Business & Management, 2021)
This study investigates the effects of team identification on consumer purchase intention in sports influencer marketing in South Korea. Specifically, it examines the mediation effect of ad content value moderated by sports influencer credibility in the relationship between team identification and purchase intention. Team identification positively affected consumer purchase intention and ad content value. Also, ad content value mediated the relationship between team identification and purchase intention. Sports influencer credibility moderated the mediation effect of ad content value on purchase intention as well as team identification. This study provides implications for planning sports influencer marketing in the South Korean market.
Keywords: 650; sports influencer marketing; sports influencer credibility; team identification; ad content value; purchase intention